Not Just Leading, But Inspiring Flow: A Structural Model Linking Altruistic Leadership to Organizational Attachment - DEMİR, Ramazan (International Journal of Contemporary Economics and Administrative Sciences, 2025)
This study was conducted to examine the effects of altruistic leadership on employees’ work-related flow experience and organizational attachment. The primary aim of the research is to assess how altruistic leadership behaviors influence employees’ motivational experiences within the work environment and to explore the role of flow experience in the relationship between leadership and organizational attachment. Given the critical role of leadership and employee attachment in sustaining service quality within the tourism industry, this research holds both theoretical and practical significance for organizational behavior literature and sectoral applications. Data were collected from 374 white-collar employees working in accommodation enterprises located in the Side region of Antalya, Türkiye. Structural equation modeling was applied to analyze the proposed relationships. The findings revealed that altruistic leadership has a significant and positive effect on employees’ flow experience, particularly enhancing absorption, work enjoyment, and intrinsic work motivation. However, the results did not support a significant relationship between flow experience and organizational attachment, nor did they confirm a direct effect of altruistic leadership on organizational attachment, organizational trust, or organizational identification. These findings suggest that while altruistic leadership effectively fosters employees’ motivational and experiential processes at the individual level, its direct influence on organizational attachment—a more complex social construct—appears limited. However, the results did not reach statistical significance for the mediating effects, indicating that flow experience did not meaningfully transmit the influence of altruistic leadership to organizational attachment